Conflict Resolution Toolbox - Furlong T. Gary (Copyright, 2005)
This book bridges the gap between theory and practice and goes beyond just one single model to present a complete toolbox - a range of models that can be used to analyze, diagnose, and resolve conflict in any situation. It shows mediators, negotiators, managers, and anyone needing to resolve conflict how to simply and effectively understand and assess the situations of conflict they face. And it goes a step further, offering specific, practical guidance on how to intervene to resolve the conflict successfully.